PERSUASIVE LEADERSHIP STYLE OF THE HEAD OF SINDANGSARI VILLAGE, CIMERAK DISTRICT PANGANDARAN DISTRICT - Dani Adiwijaya (Yayasan Panca Bakti Wiyata Pangandaran, 2023)
Study This background by Head Village not yet optimal apply style leadership persuasive in the Village Sindangsari Subdistrict Cimerak Regency Pangandaran . As for objective study This is For know style leadership persuasive Head Village Sindangsari Subdistrict Cimerak Regency Pangandaran . Method used _ in study This is descriptive analysis . Informant as many as 10 people. Technique data collection is studies bibliography , study field ( observation And interview ) and documentation . Writer use technique qualitative data analysis through processing of result data interview And observation For withdrawn conclusion so that can answer problem in study . Based on results study is known that : no _ leadership persuasive Head Village Sindangsari Subdistrict Cimerak Regency Pangandaran Not yet in accordance with characteristics leadership persuasive Because head village Not yet can influence public For can follow various programs that have been set Because lack of head village own skill in persuade all party For involved And cooperate in various activities carried out besides That lack of trust given _ head village to public Because lack of involvement public in various planned activities _ as well as lack of motivating public in follow activities to be implemented , as well lack of Power pull head village in carry out his leadership Because head village not enough awaken attention various party to activity And not enough give information available _ understood as well as lack of suitability implementation activity with results musrenbangdes . So as with results observations made _ is known that head village not enough own skill in apply style leadership persuasive Because head village not enough open in accept various input submitted _ by public in discussion village so that the persuasion conveyed For invite role active public not enough succeed because not enough intertwined cooperation in carry out activity the besides That head village not enough give trust to public For can carry out various activities carried out And lack of motivating all party For involved in a way active in various activity Because not enough understand benefit his involvement in activities carried out . Besides That head village not enough own Power pull so that Not yet can awaken attention to activities carried out Because lack of information available _ understood by public .